2020
DOI: 10.1097/iae.0000000000003083
|View full text |Cite
|
Sign up to set email alerts
|

Management of Retinal Pigment Epithelium Tear During Anti–vascular Endothelial Growth Factor Therapy

Abstract: This publication provides an overview of current evidence for the development of retinal pigment epithelium tears during anti-vascular endothelial growth factor therapy, and summarizes the recommendations of the Vision Academy Steering Committee on appropriate imaging techniques for documenting retinal pigment epithelium tears, the identification of high-risk patients, and the management of patients who develop retinal pigment epithelium tear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
1
7
1
2
Order By: Relevance
“…The safety profile of IVT-AFL over the 2-year study was consistent with that of prior observational studies [9][10][11][12][13] and no unexpected safety signals were identified. The incidence of retinal pigment epithelial tear during anti-VEGF therapy in PERSEUS-IT is similar to that reported for untreated cases of nAMD; there is no clear evidence of differing risk according to anti-VEGF agent use or type [19].…”
Section: Discussionsupporting
confidence: 66%
“…The safety profile of IVT-AFL over the 2-year study was consistent with that of prior observational studies [9][10][11][12][13] and no unexpected safety signals were identified. The incidence of retinal pigment epithelial tear during anti-VEGF therapy in PERSEUS-IT is similar to that reported for untreated cases of nAMD; there is no clear evidence of differing risk according to anti-VEGF agent use or type [19].…”
Section: Discussionsupporting
confidence: 66%
“…Tears of the RPE have been well-documented during both the natural history and treatment of wAMD, [89,90] occurring in approximately 10-12% of patients with wAMD. [91] They traditionally occur in type 1 MNV, with a large, vascularized, and often peaked PED, [92] and contracture of the MNV is thought to produce tensile forces on RPE attachment junction, eventually resulting in tearing of the RPE. As this is a structural complication of the RPE, SW-AF is particularly suited for imaging this feature.…”
Section: Age-related Macular Degeneration (Amd)mentioning
confidence: 99%
“…(J Glaucoma 2023;32:e60-e62) R etinal pigment epithelium (RPE) tear is a well-known complication of retinal pigment epithelial detachment (PED), particularly neovascularized PED in the context of age-related macular degeneration treated by intravitreal injections of anti-vascular endothelial growth factor drugs. 1 RPE tears have been described after intravitreal injections of steroids as well. It can also be a complication of laser treatments, especially photocoagulation and dynamic phototherapy.…”
mentioning
confidence: 99%